Mn(ii) mediated degradation of artemisinin based on Fe3O4@MnSiO3-FA nanospheres for cancer therapy in vivo. Issue 29 (3rd July 2015) - Chen, Jian; Zhang, Weijie; Zhang, Min; Guo, Zhen; Wang, Haibao; He, Mengni; Xu, Pengping; Zhou, Jiajia; Liu, Zhenbang; Chen, Qianwang
Abstract : Artemisinin (ART) is a natural drug with potent anticancer activities related with Mn 2+ mediated cleavage of the endoperoxide bridge in ART. Abstract : Artemisinin (ART) is a natural drug with potent anticancer activities related with Fe 2+ mediated cleavage of the endoperoxide bridge in ART. Herein, we reported that Mn 2+ could substitute for Fe 2+ to react with ART and generate toxic products, inducing a much higher anticancer efficiency. On this basis, we prepared pH-responsive Fe3 O4 @MnSiO3 -FA nanospheres which can efficiently deliver hydrophobic ART into tumors in mice models. Mn 2+ was released in acidic tumor environments and intracellular lysosomes, interacting with ART to kill cancer cells. The ART-loaded nanocarriers could suppress tumor growth more efficiently than free ART, which could be further illustrated by magnetic resonance imaging (MRI). Histological analysis revealed that the drug delivery system had no obvious effect on the major organs of mice. ART has been reported to have lower toxicity than chemotherapeutics. The ART-loaded nanocarriers are promising to be used in improving the survival of chemotherapy patients, providing a novel method for clinical tumor therapy.